The Nexus between Funding and Research Output: A Case Study in Universiti Teknologi MARA - Henry, Caroline; Azura Md Ghani, Nor; Haron, Halilah; Marshida Abd Hamid, Umi; Naqiyuddin Bakar, Ahmad; Taufek Abdul Rahman, Ahmad (International Journal of Engineering and Technology, 2018)
Financial sustainability has been a continuous problem that Higher Learning Institutions (HLI) have to face. In addition, funding has always played a role in the process of research as many have proven that there is a relationship between funding and research impact. This study highlights the impact of funding on UiTMâ€™s research productivity. Publications published by UiTM in 2012 to 2016 from Web of Science (WoS) were used to compare the impact of both funded and unfunded publications. The findings showed that 32.53% of the publications published from 2007 to 2016 were funded. Funded publications published in high impact journals have higher citations compared to unfunded publications particularly for Medical and Science & Technology related fields such as Clinical Medicine and Chemistry. This proves that financial assistance is key to drive quality research and produce impactful publications as it indirectly increases the institutionâ€™s research productivity.Â Â